PHARMACEUTICO ANALYTICAL STUDY OF ROMASHATANA LEPA - gupta, *Dinesh; Mitti, Jagdish; Patil, Mallikarjun (International Journal of Ayurveda and Pharma Research, 2015)
Unwanted hairs which are present in the body causes cosmetological as well as psychological problems for an individual. To remove the unwanted hairs there are numerous medicines and procedures, which are carried out for depilation action. These medicines are mainly chemicals have side effects and irritation to the skin. The techniques which are employed for this purpose are expensive; still the relapse of the hair occurs because these are giving temporary results. As there are so many medicines which are available in the market for the other diseases like Jwara (fever), Sandhgataivata (osteoarthritis), Amavata (rheumatoid arthritis), Amalpitta (acid peptic disorder), Shwasa (bronchial asthma), Kasa (cough) etc. but for the Romashatana there are no such frequently available medicine. The hair removal products which are available in the market are not herbal or herbomineral. Romashatana lepa is a herbomineral preparation prepared by taking Shoditha hartala, Shanka and Palasha khara. Physico-chemical analytical results of Romashatana lepa show pH 8.78, Arsenic 2.33%w/w, Calcium 22% w/w.